The modern theologians : an introduction to Christian theology in the twentieth century - Ford, David F., 1948- (Cambridge, Mass. : Blackwell Publishers, 1997)
This is a thoroughly revised and expanded edition of The Modern Theologians, first published in 1989, which is now available in a single volume. The Modern Theologians provides a comprehensive and accessible introduction to the main Christian theologies of the twentieth century, and is the ideal textbook for students at universities, colleges, and seminaries. Each chapter is written by a leading theologian and aims to give a clear picture of a particular movement, topic, or individual theologian. It also aims to further the critical debates in the field.
Introduction to modern Christian theology / David F. Ford -- Part I -- Continental European theologies -- Karl Barth / Robert W. Jenson -- Dietrich Bonhoeffer / Charles Marsh -- r Werner G. Jeanrond -- Wolfhart Pannenberg / t Richard Bauckham -- Part II. British theologies -- Theology through history / S.W. Sykes -- Theology through philosophy / Daniel W. Hardy -- Theology and society / Peter Sedgwick -- Part III. Theologies in North America -- Theological ethics / William Werpehowski -- Revisionists and liberals / James J. Buckley -- Postliberal theology / William C. Placher -- Black, Hispanic/Latino, and Native American theologies / M. Shawn Copeland -- Feminist and womanist theologies / Rebecca S. Chopp -- Part IV. Latin American, African, and Asian theologies -- Latin American liberation theology / Rebecca S. Chopp -- African theology / Kwame Bediako -- African theology : South Africa / John W. de Gruchy -- Asian theology / George Gispert-Sauch -- Part V. Evangelical and Orthodox theologies -- Evangelical theology / Ray S. Anderson -- Eastern Orthodox theology / Rowan Williams -- Part VI. Transregional movements -- Biblical theology and hermeneutics / Anthony C. Thiselton -- Ecumenical theology / Michael Root -- Theology of mission / Lamin Sanneh -- Feminist theology / Ann Loades -- Postmodern theology / Graham Ward -- Part VII. Theology and religious diversity -- Judaism and Christian theology / Peter Ochs -- Theology of religions / Gavin D'Costa -- Part VIII. Theology and the arts and sciences -- Theology and the natural sciences / Ted Peters -- Theology and the arts : visual arts / Graham Howes -- Theology and the arts : music / Jeremy Begbie -- Theology and the social sciences / Richard H. Roberts -- Epilogue : Christian theology at the turn of the millennium / David F. Ford.
Includes bibliographical references and index.
Keywords: Theology, Doctrinal -- History -- 20th century; Theologie; Dogmatiek; Theologie; y; Theology, Doctrinal; Geschichte 1900-1990.; 1900 - 1952; History